2012
DOI: 10.1371/journal.pone.0046735
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Selective Inhibition of Rho Kinase Protect Small Conductance Calcium-Activated Potassium Channel Function (KCa2.3) in Cerebral Arteries

Abstract: BackgroundIn rat middle cerebral and mesenteric arteries the KCa2.3 component of endothelium-dependent hyperpolarization (EDH) is lost following stimulation of thromboxane (TP) receptors, an effect that may contribute to the endothelial dysfunction associated with cardiovascular disease. In cerebral arteries, KCa2.3 loss is associated with NO synthase inhibition, but is restored if TP receptors are blocked. The Rho/Rho kinase pathway is central for TP signalling and statins indirectly inhibit this pathway. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…Previous studies have demonstrated that statins can modify the activities of different ion channels in blood vessels including L-type Ca 2+ channel and BK Ca channel [3], [9], [10], [11]. In addition to Ca 2+ channels and BK Ca channels, ATP-sensitive K + (K ATP ) channels are abundant in vascular tissues and K ATP channels are also important in regulating the vascular tone [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that statins can modify the activities of different ion channels in blood vessels including L-type Ca 2+ channel and BK Ca channel [3], [9], [10], [11]. In addition to Ca 2+ channels and BK Ca channels, ATP-sensitive K + (K ATP ) channels are abundant in vascular tissues and K ATP channels are also important in regulating the vascular tone [12].…”
Section: Introductionmentioning
confidence: 99%
“…Статины продемонстри-ровали также положительное влияние на артерии го-ловного мозга за счет защиты и восстановления К + Са 2+ -насоса после эндотелий-зависимой гиперполяризации. Последняя вызывается стимуляцией тромбоксановых рецепторов, что часто наблюдается при эндотелиаль-ной дисфункции [35]. Таким образом, решающее значение в снижении смертности и инвалидизации после перенесенного инсульта принадлежит первичной и вторичной про-филактике.…”
Section: Discussionunclassified
“…Middle cerebral artery function was studied in vessels mounted on an isometric wire myograph (model 410 A; Danish Myo Technology, Aarhus, Denmark) following the protocol described (McNeish et al 2012, Gauthier et al 2014. Constricted tone was induced with the stable TxA 2 mimetic 9,11-dideoxy-9a, 11amethano-epoxy prostaglandin F2a (U46619; 30-100 nmol L À1 ; EMD Millipore, Billerica, MA, USA) or endothelin-1 (1-10 nmol L À1 ; Enzo Life Sciences, Farmingdale, NY, USA).…”
Section: Wire Myographymentioning
confidence: 99%
“…Concentrations of most inhibitors were chosen based on previous studies (McNeish & Garland 2007, McNeish et al 2012, Gauthier et al 2014. Concentrations of most inhibitors were chosen based on previous studies (McNeish & Garland 2007, McNeish et al 2012, Gauthier et al 2014.…”
Section: Wire Myographymentioning
confidence: 99%
See 1 more Smart Citation